Battery module with polyorganosiloxane foam barrier
By using a barrier material composed of polyorganosiloxane foam, flame retardant and expanded perlite in the battery module, the problem of insufficient thermal insulation in the high-energy density battery pack is solved, and improved heat resistance and flame retardancy are achieved. Reduces thermal runaway and explosion risks.
Patent Information
- Application Number
- CN202280096349.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-27
- Publication Date
- 2025-01-03
AI Technical Summary
The existing battery modules are insufficient thermal insulation in high-energy density battery packs, resulting in thermal runaway and explosion risks. The traditional thermal barrier materials have poor mechanical elasticity, making it difficult to meet the needs of thermal insulation, flame retardancy and compressibility.
Using barrier materials composed of polyorganosiloxane foam, flame retardant and expanded perlite, the reaction of polydimethylsiloxane functionalized with hydroxyl-containing compounds and hydrosil addition catalysts by modifying the reaction of Si-H group-functionalized polydimethylsiloxane with hydroxyl-containing compounds and hydrosil addition catalysts Insulating, compressible and flame-retardant foaming materials with density of 0.10 g/cm3 to 0.90 g/cm3 are formed as barriers between battery cells.
It provides improved heat and flame retardant properties, meeting the thermal insulation, flame retardant and compressibility requirements of high-energy density battery packs, reducing thermal runaway and explosion risks.
Smart Images

Figure BDA0005145564940000061 
Figure BDA0005145564940000071 
Figure HDA0005145564960000011
Abstract
Description
Background Art
[0001] The present invention relates to battery modules insulated with treated polyorganosiloxane foam barriers.
[0002] Rechargeable batteries such as lithium-ion batteries (LiBs) are commonly used in a variety of applications, including electric vehicles (EVs) and grid energy storage systems. Although LiBs have the desirable properties of high energy density and stability, safety issues currently limit their usefulness. First, failure of LiB cells can be triggered due to manufacturing defects, internal short circuits, overheating, overcharging, or mechanical shock; second, the heat generated from a failed cell can propagate, causing thermal runaway in adjacent cells. The rapid pressure buildup caused by these thermal events increases the risk of fire and explosion.
[0003] Thermal runaway can be mitigated by placing a thermal barrier between the cells in the LiB module, which provides thermal insulation and flame retardancy. Commonly used thermal barriers such as aerogels, ceramic fibers, and mica boards provide such properties; however, aerogels and ceramic fibers have poor mechanical elasticity, while mica boards have poor compressibility. On the other hand, although silicone foam foam provides sufficient compressibility and is therefore suitable for low and medium energy density batteries, its thermal insulation is insufficient to prevent thermal runaway for very high energy density battery packs. Therefore, in the field of thermal barriers for rechargeable batteries, it is desirable to produce a barrier that provides thermal insulation, flame retardancy, and satisfactory compressibility. Summary of the invention
[0004] The present invention solves the need in the art by providing a battery module comprising a housing containing an array of spatially separated battery cells and a barrier material contacting adjacent battery cells, wherein the barrier material comprises 35 wt % to 95 wt % of a polyorganosiloxane foam based on the weight of the barrier material; 1 wt % to 30 wt % of a flame retardant; and 1 wt % to 15 wt % of expanded perlite; wherein the barrier material has a viscosity of 0.10 g / cm 3 Up to 0.90g / cm 3 Density within the range.
[0005] The battery module of the present invention provides improved heat resistance and flame retardant properties for applications such as lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figure 1 is a diagram of a battery module containing a polyorganosiloxane foam material. DETAILED DESCRIPTION
[0007] The present invention is a battery module comprising a housing containing an array of spatially separated battery cells and a barrier material contacting adjacent battery cells, wherein the barrier material comprises 35 wt % to 95 wt % of a polyorganosiloxane foam based on the weight of the barrier material; 1 wt % to 30 wt % of a flame retardant; and 1 wt % to 15 wt % of expanded perlite; wherein the barrier material has a viscosity of 0.10 g / cm 3 Up to 0.90g / cm 3 Density within the range.
[0008] The barrier material as thermally insulating, flame retardant and compressible foamed polyorganosiloxane can be prepared by modifying the method described in US Pat. No. 5,358,975. For example, it is advantageous to use a polydimethylsiloxane (a) functionalized with at least two, and preferably at least three Si-H groups in contact with one or more hydroxyl-containing compounds (which are water, alcohols, diols, polyols) or compounds containing at least one silanol group (b), a divinyl-functionalized polydimethylsiloxane (c), a hydrosilylation catalyst such as a platinum-based catalyst (d), a flame retardant (e) and expanded perlite (f) to form a crosslinked network of insulating, compressible and flame retardant foamed material having -Si-CH2-CH2-Si- groups and -Si-OR groups (where R is H or a structural unit (i.e., a reaction product) of an alcohol, diol, polyol or silanol). The total amount of component (a), component (b) and component (c) is from 35% by weight or from 40% by weight to 80% by weight or to 70% by weight of the polyorganosiloxane foam.
[0009] It may be advantageous to prepare the barrier material using a 2-part process, wherein in a first container, a first part of a divinyl-functionalized polydimethylsiloxane; a first part of a flame retardant; a hydrosilylation catalyst; one or more hydroxyl-containing compounds; and a first part of expanded perlite are blended to form a Part A composition. In a second container, the remaining part of the divinyl-functionalized polydimethylsiloxane; a polymer resin blend, which is a mixture of a divinyl-functionalized polydimethylsiloxane and a crosslinked organopolysiloxane resin; the remaining part of the flame retardant; a polydimethylsiloxane functionalized with at least three Si-H groups; and the remaining part of the expanded perlite are blended to form a Part B composition. Parts A and B are then combined and mixed, and then poured between two release film sheets to form the foamed material of the present invention.
[0010] The flame retardant is a metal hydroxide, carbonate, hydroxide-carbonate or hydrate that releases CO2 or water or both when heated. Examples of flame retardants include Al(OH)3, Mg(OH)2, Ca(OH)2MgCO3·3H2O (nesquehonite), Mg5(CO3)4(OH)2·4H2O (hydromagnesite), MgCa(CO3)2 (calcium carbonate), AlO(OH) (boehmite), NaHCO3 and hydrated MgSO4 (epsomite). The polyorganosiloxane foaming material contains from 1 wt% or from 2 wt% or from 3 wt% to 30 wt% or to 20 wt% or to 15 wt% of the flame retardant based on the weight of the foaming material.
[0011] The barrier material also includes 1 or 2 weight percent to 15 or to 10 weight percent expanded perlite. Expanded perlite can be formed by rapidly heating perlite ore to a temperature in the range of 750°C to 1000°C. The resulting expanded particles typically have a particle size of 0.03 g / cm 3 Up to 0.20g / cm 3 Using a dynamic light scattering analyzer such as Beckman Coulter LS130 particle size analyzer, the average volume particle size is generally in the range of 0.1 μm to 1000 μm.
[0012] The obtained barrier material has a thermal conductivity of 0.10 g / cm 3 or 0.15g / cm 3 Up to 0.90g / cm 3 Or up to 0.50g / cm 3 Density within the range.
[0013] In another aspect, the present invention is a composition comprising, based on the weight of the composition, a) 2 to 50 weight percent of a polysiloxane functionalized with at least two Si-H groups and having a degree of polymerization in the range of 5 to 1000; b) 1 to 50 weight percent of water, an alcohol, a diol, a polyol, or a compound containing one or more silanol groups; c) 10 to 90 weight percent of a polysiloxane functionalized with at least one ethylenically unsaturated group and having a degree of polymerization in the range of 20 to 2000; wherein the total concentration of components a, b and c ranges from 35 to 95 weight percent, based on the weight of the composition; d) a catalytic amount of a hydrosilylation catalyst; e) 1 to 30 weight percent of a flame retardant; and f) 1 to 35 weight percent of expanded perlite.
[0014] Figure 1Represents one embodiment of the present invention. The battery module includes a housing (20) that houses an array of spatially separated battery cells (30 and 30a) and a barrier material (40) that contacts adjacent battery cells, thereby creating an insulating barrier between the battery cells (30). In this embodiment, the barrier material is positioned between adjacent battery cells (30). In another embodiment, the barrier material covers the battery cells. The battery module may also include an end plate (50) at the inner edge of the housing, which is in direct contact with the battery cells (not shown) or indirectly in contact with the battery cells through a barrier foam (30a). The barrier material can be inserted into the space between adjacent battery cells and between the cells and the end plate; alternatively, a foam precursor can be applied to the cell and into the space between the battery cells, and then cured to form the barrier material.
[0015] Examples of suitable battery cell designs include cylindrical, pouch, and prismatic cells. Particularly advantageous modules include pouch or prismatic cells with preformed barrier material in the form of foam sheets positioned between the cells during assembly. For cylindrical designs, a precursor foam material is typically dispensed into the spaces separating the cylindrical cells and then cured to form a barrier material surrounding the cylindrical cells.
[0016] It has been discovered that battery modules having barrier materials as described herein provide the desirable properties of thermal insulation, flame retardancy, and compressibility in rechargeable battery thermal barrier applications.
[0017] In the following examples, ViMe2SiO 1 / 2 / (CH3)3Si-O 1 / 2 / SiO 4 / 2 Resin M w and M n It was determined by gel permeation chromatography (gpc) using a gpc column filled with divinylbenzene cross-linked polystyrene beads of pore type Mixed-C (Polymer Laboratory) of 5-mm diameter size. Tetrahydrofuran was used as the mobile phase and detection was performed by a refractive index detector.
[0018] In the following examples, ViMe2SiO 1 / 2 / (CH3)3Si-O 1 / 2 / SiO 4 / 2 Resin M w and M n It was determined by gel permeation chromatography using a gpc column filled with divinylbenzene cross-linked polystyrene beads of pore type Mixed-C (Polymer Laboratory) of 5-mm diameter size. THF was used as the mobile phase and detection was performed by a refractive index detector.
[0019] Example 1 - Preparation of Foamed Organopolysiloxane Articles with Expanded Perlite Particles
[0020] The first component (Part A) was prepared by mixing together using a Flacktek Speed mixer: a dimethylvinylsiloxy terminated polydimethylsiloxane having a viscosity of about 40,000 mPas (Polymer 1, 11.0 pbw); 1) a dimethylvinylsiloxy terminated polydimethylsiloxane having a viscosity of about 1,900 mPa·s and about 0.22 wt% Vi; and 2) ViMe2SiO 1 / 2 :(CH3)3Si-O 1 / 2 :SiO 4 / 2 The structural unit ratio is 5:40:55, M n is 5000 and M w 21,400 ViMe2SiO 1 / 2 / (CH3)3Si-O 1 / 2 / SiO 4 / 2 64:36 w / w blend of resin (polymer-resin blend, 62.9 pbw); and Micral 855 aluminum hydroxide (14.7 pbw). The contents were stirred at 2000 rpm for 30 seconds, after which a complex of Pt(0) and divinyltetramethyldisiloxane (0.9 pbw, 0.62 wt% Pt), 1,4-butanediol (2.5 pbw) and benzyl alcohol (3.2 pbw) were added to the mixture and the contents were stirred at 2000 rpm for 30 seconds. Finally, Omyasphere TP-312FQ expanded perlite particles (average volume average particle size of 63 μm; 4.8 pbw) were added to the mixture and the contents were stirred at 2000 rpm for 30 seconds.
[0021] A second composition (Part B) was similarly prepared by mixing together Polymer 1 (8.6 pbw), Polymer Resin Blend (49.5 pbw), and Hymod M855 aluminum hydroxide (25.6 pbw). The contents were stirred at 2000 rpm for 30 seconds, after which a linear organohydrogenpolysiloxane having a viscosity of 30 mPa·s and a 1.6 wt% SiH content (6.5 pbw) and a polydimethylorganohydrogensiloxane having a viscosity of 5 mPa·s and a 0.7 wt% SiH content (4.9 pbw) were added to the mixture, and the contents were stirred at 2000 rpm for 30 seconds. Omyasphere TP-312FQ expanded perlite particles (average volume average particle size of 63 μm; 4.8 pbw) were then added to the mixture, and the contents were stirred at 2000 rpm for 30 seconds.
[0022] Equal amounts of Part A and Part B were then mixed and the mixture was poured between two release films (matte mylar film). The initial (pre-foaming) thickness was controlled at 0.045 inches using a nip roller. The sample was cured at 70°C for 5 minutes and then at 100°C for 15 minutes to produce a foam sheet for further testing. (Density = 0.29 g / cm 3 )
[0023] Example 2 - Preparation of Foamed Organopolysiloxane Articles with Expanded Perlite Particles In addition to using Omyasphere 235T-FQ expanded perlite particles (average volume average particle size of 124 μm, 4.8 pbw) (density = 0.31 g / cm 3 ), the method for preparing the foamed article of Example 1 is carried out in substantially the same manner.
[0024] Example 3 - Preparation of Foamed Organopolysiloxane Articles with Expanded Perlite Particles In addition to using Omyasphere 235T-FQ expanded perlite particles (9.1 pbw) (density = 0.35 g / cm 3 ), the method for preparing the foamed article of Example 1 is carried out in substantially the same manner.
[0025] Comparative Example 2 - Preparation of Foamed Organopolysiloxane Articles with Hollow Glass Beads
[0026] In addition to using 3M iM16K hollow glass beads (average volume average particle size of 20 μm, 20 pbw) (density = 0.28 g / cm 3 ), the method for preparing the foamed article of Example 1 is performed in substantially the same manner except that the amount of beads is selected to obtain a filler volume similar to that of the expanded perlite in Example 1.
[0027] Thermal insulation and flammability
[0028] The thermal insulation and flammability of the foams prepared as described in the examples were tested using a hot plate set on a hydraulic press. The hot plate was set at 600°C with an insulator on top of the surface. Four thermocouples (type K) were fixed to an aluminum heat sink (4" x 4" x 0.47") using Kapton tape. The sample (4" x 4") was then placed and fixed to the heat sink using Kapton tape. Another thermocouple (type K) was attached to the sample surface using Kapton tape. The insulator was removed from the hot surface and the sample attached to the heat sink was quickly placed on the hot surface so that the sample surface faced the hot plate surface and the Al heat sink faced the opposite side. The pressure was quickly increased to 355kPa. The interface temperature between the hot plate surface and the sample surface and the interface temperature between the sample surface and the heat sink were recorded using a data logger. Once the time reached 300 seconds, the pressure was released and the test was terminated. Sample surface temperatures <300°C were considered acceptable. No observable flames throughout the test were considered acceptable flame retardancy.
[0029] hardness
[0030] Measure hardness using a Shore 00 durometer. Place the test specimen on a hard, flat surface. Then press the indenter of the Shore 00 durometer onto the specimen, making sure it is parallel to the surface. Read the hardness during firm contact with the specimen. A hardness of <80 is considered acceptable.
[0031] Compression force
[0032] The compressive force was measured using a TA.HDplus Texture Analyzer equipped with a 100kg load cell, a 40mm diameter aluminum probe, and a flat heavy-duty aluminum substrate. The silicone foam sample was cut into a circle using a 1" diameter die cut and placed between the substrate and the probe. The probe was initially set at the same height as the sample thickness and lowered at a rate of 1mm / s until the pressure reached a maximum. The sample thickness and pressure were recorded as a compression force curve. The pressure was recorded at 30% of the initial sample thickness. A compression force of <500kPa was considered acceptable.
[0033] Foam density
[0034] The foam density was calculated based on the average thickness and weight of two foam samples having a diameter of 1 inch.
[0035] The properties of the expanded perlite-filled organopolysiloxane article were compared with two other foams: Comparative Example 1, which is a commercial organopolysiloxane article (COHRlastic silicone foam, available from Stockwell Elastomerics) that is similar in construction to the example foam except that it does not contain expanded perlite; and Comparative Example 2, which is a foam containing 3M Glass Bubbles iM16K hollow glass microspheres.
[0036] Table 1 summarizes the performance characteristics of the foams of Examples 1-3, commercial comparative foams, and foams containing hollow glass microspheres. Density in g / cm 3 Measurements; hardness is measured in Shore 00 units; compression (Force) is measured in kPa at 30% compression; temperature at 600°C (T after 300 seconds) refers to the sample surface temperature after 300 seconds; and flammability refers to the observability of flames during the thermal insulation test.
[0037] TP-312-FQ refers to Omyasphere TP-312-FQ expanded perlite; 235T-FQ refers to Omyasphere 235-T-FQ expanded perlite; and iM16K refers to 3M Glass Bubble iM16K hollow glass microspheres.
[0038] Table 1 - Properties of organopolysiloxane products
[0039]
[0040]
[0041] Table 1 shows that the foam of the present invention containing expanded perlite passed all tests, while the sample without expanded perlite (Comparative Example 1) failed the thermal insulation test, and the sample with hollow glass microsphere filler (Comparative Example 2) failed the compression test.
Claims
1. A battery module comprising a housing containing an array of spatially separated battery cells and a barrier material contacting adjacent battery cells, wherein the barrier material comprises 35 wt % to 95 wt % of a polyorganosiloxane foam based on the weight of the barrier material; 1 wt % to 30 wt % of a flame retardant; and 1 wt % to 15 wt % of expanded perlite; wherein the barrier material has a viscosity of 0.10 g / cm 3 Up to 0.90g / cm 3 Density within the range.
2. The battery module according to claim 1, wherein the barrier material comprises 50 wt % to 80 wt % of the polyorganosiloxane foam, 2 wt % to 20 wt % of the flame retardant, and 2 wt % to 10 wt % of expanded perlite, based on the weight of the barrier material.
3. The battery module according to claim 2, wherein the flame retardant is Al(OH)3, Mg(OH)2, MgCO3·3H2O, or Mg5(CO3)4(OH)2·4H2O, MgCa(CO3)2, AlO(OH), NaHCO3 or hydrated MgSO4 or a combination thereof.
4. The battery module according to any one of claims 1 to 3, wherein the barrier material has a relative humidity of 0.15 g / cm 3 Up to 0.50g / cm 3 Density within the range. 5 . The battery module according to claim 1 , comprising pouch-shaped or prismatic battery cells and a sheet of the barrier material positioned between adjacent battery cells. 6 . The battery module according to claim 1 , comprising cylindrical battery cells, wherein the barrier material surrounds the cylindrical battery cells.